INTERDEPENDENSI VARIAN DINAMIS DAN TRANSMISI VOLATILITAS PADA PASAR SAHAM ASEAN - Intan Purbasari (Tirtayasa Ekonomika, 2017)
This paper investigates the interdependence of volatility in five South East Asian Markets. First, modeled the returns in a VAR-BEKK framework to obtain the conditional variances, and then apply the vector-autoregressive model (VAR) to the five market variances. The result of VAR estimation show that the interdependence of equity market conditional variances is high. The Singapore market, while being the most exogenous and least susceptible to volatility stimuli from other markets, is the most influential in transmitting volatility to the other ASEAN markets